Pengaruh Penambahan Sari Buah Apel Terhadap Nilai Ph Dan Jumlah Bakteri Asam Laktat Pada Soyghurt - Kinanthi, Dinnar; Eni Purwani, Eni Purwani S.Si., M.Si (2016)
Background : Soy milk is a good protein source and can be used as alternatives to cow's milk and can be consumed by individual who experiences intolerance lactose. However, soy milk has unpleasant odors and less desirable favor, to overcome those problems create fermented soy milk soyghurt) that serves as a preservative, adder flavor, and help improve the digestive tract. Objective : Know the effect of adding cider on the pH value and the number of lactic acid bacteria on soyghurt. Research Methods : This was a experimental study .This research is written by adding the percentage of cider as many as 0 % , 15 % and 30 % into soyghurt at two times, then see the ph values and the number of lactic acid bacteria using colony counter and statistic analysis is done by Kruskal wallis. Results : There's a influence between cider with pH value and the number of lactic acid bacteria in soyghurt.The results of the best percentage based on the analysis of ph values and the number of lactic acid bacteria is 15 % . Conclusion : In the next research can be done with sensory test in cider soyghurt that is be useful to know the quality of cider soyghurt cider and by soyghurt sensory test . Keyword :apple cider, pH value, the number of lactic acid bacteria, soyghurt.